HUBUNGAN KUALITAS PELAYANAN DENGAN REKOMENDASI MAHASISWA - Euis Winarti (POLITEKNIK LP3I JAKARTA, 2012)
The Relationship between Service Quality with the Student's Recommendation.The benefit of this research is expected, to become the guidance for the managerial, mainly in upgrading the service quality in term of upgrading the student's recommendation.The purpose of this research is to examine the hypothesis of relationship between Service Quality with Student's Recommendation. In drawing the sample used